Paul's Fundamental Immunology - Flajnik, Martin F; Singh, Nevil J.; Holland, Steven M. (New Delhi : Wolters Kluwer, 2023)
Defining the field of immunology for 40 years, Paul$1 (Bs Fundamental Immunology continues to provide detailed, authoritative, up-to-date information that uniquely bridges the gap between basic immunology and the disease process. The fully revised 8th edition maintains the excellence established by Dr. William E. Paul, who passed away in 2015, and is now under new editorial leadership of Drs. Martin F. Flajnik, Nevil J. Singh, and Steven M. Holland. It$1 (Bs an ideal reference and gold standard text for graduate students, post-doctoral fellows, basic and clinical immunologists, microbiologists and infectious disease physicians, and any physician treating diseases in which immunologic mechanisms play a role.s
Includes index
Keywords: Immunologic diseases; Immune system; Immunogenetics; Immunochemistry